Five Have Plenty Of Fun - Blyton, Enid (London Hodder Children's Books, 2015)
New and contemporary cover treatment brings The Famous Five into the 21st Century, and to a whole new generation of readers!
Keywords: Children's Literature - Fiction : Adventure